Brazil - Forests in the Balance : Challenges of Conservation with Development - Lele, Uma; Viana, Virgilio; Verissimo, Adalberto; Vosti, Stephen; Perkins, Karin; Husain, Syed Arif (World Bank, Washington, DC, 2014)
This case study is one of six evaluations of the implementation of the World Bank's 1991 Forest Strategy. This and the other cases (Cameroon, China, Costa Rica, India, and Indonesia) complement a review of the entire set of lending and nonlending activities of the World Bank Group and the Global Environment Facility. The World Bank has clearly diminished its lending presence in the Amazon in the past decade. It has moved from the "big projects" era of the 1960s through the 1980s and strong economic and sector work to a more careful approach at the end of the century with attempts once again to focus on strategic issues and smaller projects, including pilot activities. This seems due both to the poor performance of earlier projects-which prompted a more risk-adverse Bank strategy following the intense international scrutiny and criticism contributing to the cautious approach urged by the 1991 Forest Strategy-and to a lack of demand in Brazil for Bank funds. Brazil's macroeconomic difficulties-its balance of payments and fiscal deficits-have led the government to be selective as well as to shift lending to quick-disbursing activities. This is evident in the most recent land reform programs. Controlling deforestation is not easy given the large number and level of national and global forces and actors affecting it. If the Bank is to be a facilitator for balancing the needs of stakeholders (i.e., the poor and the indigenous people) and national and global interests, it must be seen as an objective bystander. The 1991 Forest Strategy emphasizes the primacy of the rights of the indigenous people-and by implication their rights have primacy over those of the local poor. But the Bank cannot be a facilitator unless it is viewed by both parties as not serving the interests of only one party.